The selective catalytic reduction of nitric oxide by propylene over bimetallic CeO2-ZrO2 supported catalyst - Chong, Chee Ming (2005)
Air pollution by nitrogen oxides (NOx) is currently one of the most serious environmental problems. The conventional three-way catalyst shows low NOx conversion in lean burn exhaust that contains high concentration of O2. The selective catalytic reduction of NO (SCR-NO) with C3H6 in the presence of excess O2 over bimetallic Cu-Ag catalysts supported on CeO2-ZrO2 was investigated in this study. Initially, it was found that the loading of Ag strongly promoted the catalytic performance of Cu(4)/CeO2 catalyst, reaching a maximum NO conversion with the doping of 1 wt% Ag. The UV-Vis DRS results revealed that the major species on Cu(4)/Ag(1)/CeO2 catalyst were isolated Cu2+ species and Agn 􀄯+ clusters which are responsible toward a higher NO reduction activity. However, Cu(4)/Ag(1)/CeO2 catalyst is not a promising catalyst for practical use due to its low activity in the temperature region of 250-350ºC. Extended studies were conducted to investigate the influence of different supports on the activity of SCR-NO. Cu(4)/Ag(1)/CeO2(75)-ZrO2(25) catalyst was observed to demonstrate higher NO conversions at low temperature region than the Cu(4)/Ag(1)/CeO2 catalyst due to its strong metal-support interaction and high reducibility. It is presumed that these features would enhance the activation of C3H6 to selectively react with NO at low temperature region. Central composite design coupled with response surface methodology was employed to study the effect of operating variables on the SCR activity of Cu(4)/Ag(1)/CeO2(75)-ZrO2(25) catalyst and to determine the optimum NO conversion. The ranges of the temperature, NO concentration and C3H6 concentration used in this study were 224-576ºC, 818-2582 ppm and 818-2582 ppm , respectively as determined by the central composite design. The optimum NO conversion of 82.89% was obtained at 415.38ºC, 1827.16 ppm of NO concentration and 1908.13 ppm of C3H6 concentration. A Langmuir-Hinshelwood kinetic model was proposed for this study over Cu(4)/Ag(1)/CeO2(75)-ZrO2(25) catalyst. Prediction from the model agreed well with the experimental results. The model indicated that the surface reaction between adsorbed NOx species and partially oxidized hydrocarbon was the rate-limiting step for this process.